Cytokine changes in patients with heatstroke during pilgrimage to Makkah - I. A. Hashim; A. Al-Zeer; S. Al-Shohaib; M. Al-Ahwal; A. Shenkin (Mediators of Inflammation)
Circulating levels and role of IL-6, IL-1ra, TNFsr-II and CRP in patients with heatstroke is not fully known. This study correlated levels of these mediators with outcome in 26 patients. In survivors (n=20), IL-6 concentration declined on cooling, whereas in non-survivors levels continued to increase at 6 h following admission before declining. Admission TNFsr-II concentrations in survivors were significantly lower than non-survivors and levels continued to rise in both groups. IL-1ra levels were markedly elevated in both groups. Changes in cytokine levels were not influenced by renal function. Elevated C-reactive protein levels were observed for both groups and remained so despite cooling, furthermore, there was no correlation with alanine aminotransferase levels. The study demonstrated the elevation of the above mediators and suggested a role in the pathogenesis of heatstroke. Markedly elevated levels or those that remained elevated despite cooling were associated with mortality.